Peningkatan Penggunaan Aplikasi Asesmen Kompetensi Minimum Dan Video Pembelajaran Animasi (Viber) - Mita Puspita; Nur Halizah; Elfahmi Lubis; Septina Lisdayanti; Rahmadhona Kusuma Yudha (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
students, parents are required to be able to adapt to technological advances in the learning process. The development and use of computer technology in the education system can make reforms for a better education system. Until now, forcing the learning process to continue to maintain the stability of delivering material to students. The state of the ability to master information technology between students, teachers and parents there is a gap. These various abilities force equalization of abilities, thereby minimizing the failure of abilities in delivering and receiving material during the learning process. For this reason, assistance, socialization and training are needed so that technology mastery is better. The existence of a gap in understanding and ability of information technology is a problem in itself when learning online in the current era. This activity was carried out at SDN 95 Bengkulu Selatan, Bengkulu Province. The goal is to improve the quality of learning, while the product of the service results is learning media to support the student learning process to help minimize the gap in information technology mastery and help technology-based learning to be carried out well and the absorption of material during learning can be maximized. From the minimal adequacy assessment carried out by sampling on grade 5 students, significant results were obtained, namely an 80% increase in problem solving ability between pre-test and post-test